Weight of evidence approach in dredge material management: What is it and how is it used? A UK perspective - Jemma-Anne Lonsdale; Simone de Winter; Joe Perry; Claire Mason; Charlotte Clarke; Sylvia Blake; Kirsty Clarke (Marine Policy, 2026)

Gaseous carbon dioxide removal from composting of biomass and cotton textile waste - Ethan Woods; Perry Berlin; Jesse Daystar; William Joe Sagues (Waste Management, 2025)

Ingestible identity: pigs in pagan ritual in Aelia Capitolina (Roman Jerusalem) between the Second Temple period and early Christianity - Lee Perry-Gal; Tehillah Lieberman; Joe Uziel (Archaeological and Anthropological Sciences, 2024)

Using knowledge to care for country: Indigenous-led evaluations of research to adaptively co-manage Kakadu National Park, Australia - Cathy J. Robinson; Jennifer Mairi Macdonald; Michael Douglas; Justin Perry; Samantha Setterfield; Dennis Cooper; Maria Lee; Jonathan Nadji; Sean Nadji; Alfred Nayinggul; Anita Nayinggul; Kenneth Mangiru; et al. (Sustainability Science, 2022)

Enhancing gardens as habitats for soil-surface-active invertebrates: should we plant native or exotic species? - Andrew Salisbury; Sarah Al-Beidh; James Armitage; Stephanie Bird; Helen Bostock; Anna Platoni; Mark Tatchell; Ken Thompson; Joe Perry (Biodiversity and Conservation, 2020)

Better Regional Ocean Observing Through Cross-National Cooperation: A Case Study From the Northeast Pacific - John A. Barth; Susan E. Allen; Edward P. Dever; Richard K. Dewey; Wiley Evans; Richard A. Feely; Jennifer L. Fisher; Jonathan P. Fram; Burke Hales; Debby Ianson; Jennifer Jackson; Kim Juniper; et al. (Frontiers in Marine Science, 2019)

Enhancing gardens as habitats for plant-associated invertebrates: should we plant native or exotic species? - Andrew Salisbury; Sarah Al-Beidh; James Armitage; Stephanie Bird; Helen Bostock; Anna Platoni; Mark Tatchell; Ken Thompson; Joe Perry (Biodiversity and Conservation, 2017)

EFSA Guidelines on the environmental risk assessment of genetically modified animals in the EU: the process and risk assessment considerations - Sylvie Mestdagh; Yann Devos; Christina Ehlert; Yi Liu; Nancy Podevin; Stefano Rodighiero; Elisabeth Waigmann; József Kiss; Joe N. Perry; Jeremy B. Sweet (Journal of Consumer Protection and Food Safety, 2014)

EFSA’s scientific activities and achievements on the risk assessment of genetically modified organisms (GMOs) during its first decade of existence: looking back and ahead - Yann Devos; Jaime Aguilera; Zoltán Diveki; Ana Gomes; Yi Liu; Claudia Paoletti; Patrick du Jardin; Lieve Herman; Joe N. Perry; Elisabeth Waigmann (Transgenic Research, 2014)

The spatial distribution of canopy-resident and ground-resident cereal aphids (Sitobion avenae and Metopolophium dirhodum) in winter wheat - Linton Winder; Colin J. Alexander; Chris Woolley; Joe N. Perry; John M. Holland (Arthropod-Plant Interactions, 2013)

Feral genetically modified herbicide tolerant oilseed rape from seed import spills: are concerns scientifically justified? - Yann Devos; Rosemary S. Hails; Antoine Messéan; Joe N. Perry; Geoffrey R. Squire (Transgenic Research, 2012)

Monoclonal antibodies reveal changes in predator efficiency with prey spatial pattern - GEORGIANNE J. K. GRIFFITHS; COLIN J. ALEXANDER; JOHN M. HOLLAND; PETER J. KENNEDY; JOE N. PERRY; WILLIAM O. C. SYMONDSON; LINTON WINDER (Molecular Ecology, 2008)
Spatially explicit predator–prey interactions can alter the predatory potential of natural enemies augmented through conservation biological control. To test hypotheses regarding such interactions and predatory efficiency, we used a combination of molecular techniques and mark–release–recapture to study the foraging behaviour of a generalist carabid predator, Poecilus cupreus , in response to spatial patterns of its cereal aphid prey ( Metapolophium dirhodum and Sitobion avenae ). Beetle and aphid numbers were measured across two grids of sampling locations, within which aphid spatial pattern had been manipulated to generate patchy and more homogenous distributions. Aphid consumption was measured by enzyme‐linked immunosorbent assays (ELISA) of beetle gut contents, using an aphid‐specific monoclonal antibody. Movement and distribution patterns suggest that P. cupreus does not aggregate at, nor instigate prey‐taxis within, aphid patches. However, more than two‐thirds of the 2169 P. cupreus tested by ELISA had consumed aphids and the proportion of beetles containing aphid proteins was positively related to aphid density. Against expectation, the proportion of predators feeding on aphids was greatest where prey were homogenously distributed, and this was attributed to the loss of partial refuges for prey in aphid patches. The functional value of this type of uniform foraging strategy is ideally suited to early colonization of the crop habitat, when aphid numbers are low, before populations build up and form strong spatial patterns.

Large-Scale Temporal Changes in Spatial Pattern During Declines of Abundance and Occupancy in a Common Moth - Kelvin F. Conrad; Joe N. Perry; Ian P. Woiwod; Colin J. Alexander (Journal of Insect Conservation, 2006)

East Atlantic teleconnection pattern and the decline of a common arctiid moth - Kelvin F. Conrad; Ian P. Woiwod; Joe N. Perry (Global Change Biology, 2003)
Teleconnection patterns are large‐scale atmospheric circulation systems and variation in them is often associated with impacts on climate and weather over broad areas. Arctia caja L. is a well‐known, widespread and charismatic tiger moth. In recent decades, the abundance of A. caja in UK has fallen abruptly. The annual abundance of A. caja in UK is known to be affected adversely by wet winter weather and warm spring temperatures. We examined A. caja population dynamics from 1968 to 1999 for weather and climatological effects. Population growth rate displayed endogenous effects of abundance in the previous two seasons. Accounting for this, growth rate in the present season was still affected significantly by winter precipitation and spring temperature. Annual abundance of A. caja was inversely related to winter East Atlantic teleconnection pattern (winter EA index) and annual population growth rate was inversely related to winter EA in the present and previous two seasons. An index of the North Atlantic Oscillation (NAO), commonly used as an indicator of winter climate in northern Europe, did not show a significant relationship with growth rate. We noted, for the first time, that the winter EA index has increased steadily over the past five decades. The model presented here therefore implies a further decline of A. caja population growth rates and abundance in the future. This is the first demonstration of a relationship between EA and population dynamics and indicates the EA and other lesser‐known teleconnection patterns may prove useful in modeling the ecological effects of climate change.

Modelling the dynamic spatio‐temporal response of predators to transient prey patches in the field - Linton Winder; Colin J. Alexander; John M. Holland; Chris Woolley; Joe N. Perry (Ecology Letters, 2001)
The spatio‐temporal dynamics of two aphid species ( Metopolophium dirhodum and Sitobion avenae ) and a generalist predator ( Pterostichus melanarius ) were observed in a field‐scale study using a grid of 256 sampling locations with a 12‐m spacing. Using Spatial Analysis by Distance Indices we demonstrate that populations show ephemeral spatial pattern at the field scale. We observed a positive, lagged beetle response to this aphid pattern; conversely, the aphids displayed a negative, lagged response to beetle spatial pattern. Examination of the local structure of the spatio‐temporal dynamics revealed a strong response by the beetle population to aphid patches. The temporal structure of spatial associations between the species shows a strong correspondence with those from a conceptual model of predator–prey spatial interaction. The spatially coupled dynamics were sufficiently strong for the predator to have a negative effect on the intrinsic rate of increase of their prey.

An abundance–occupancy time‐lag during the decline of an arctiid tiger moth - Kelvin F. Conrad; Joe N. Perry; Ian P. Woiwod (Ecology Letters, 2001)
The positive interspecific abundance–occupancy relationship is one of the most general patterns in ecology. Positive intra specific relationships should also exist within species over time, and so a species should occupy more sites in years when it is more abundant. However, positive intraspecific relationships are not as ubiquitous as their interspecific counterparts. It has been hypothesized that low levels of temporal variation and time‐lags between changes of abundance and occupancy within species make positive intraspecific relationships difficult to detect. We analyse 31 years of U.K.‐wide data on the decline of an arctiid moth, Arctia caja , which provides the first empirical demonstration of an abundance–occupancy time‐lag for any species. Such time‐lags are probably common and we discuss their impact on the intraspecific abundance–occupancy relationship and their implications for conservation management. In A. caja , the time‐lag indicates that the decline of the species is probably not driven by habitat loss.